The Other Non-Numerical Definitions of the Numerical “liang” at the Sentence Level : a Comparative Study with Thai Language - Chamsuwanwong, Nattanit (Journal of Sinology (วารสารจีนวิทยา), 2013)
In Chinese language, the numeral “2” (“二” èr,“两” liǎng) does not only specify an exact cardinality, but sometimes it expresses a non-exact numeral meaning, in other words represents other definitions. This paper aims to discuss some factors, in a sentence level, which cause the Chinese numeral “两” (liǎng) to represent other interpretations than the result of one plus one (1+1), such as: 1) the result of one plus one, combined simultaneously with the definition of “full”, as in “两手灰” (liǎng shǒu huī <two hands dust>, ‘both hands completely/entirely covered with dust’ ) or “两脚泥” ( liǎng jiǎo ní <two feet mud>, ‘both feet completely/entirely covered with mud’). 2) a partial quantity, like in “你说两句吧” (Nǐ shuō liǎng jù ba <you say two sentences “ba” particle>, which means ‘Say something please’) or in “他没吃两块儿饼干就饱了。” (Tā méi chī liǎng kuài bǐnggān jiù bǎo le <he didn’t even have two cookies, immediately felt full “le” particle>, ‘He just had little biscuits and felt full’). Moreover, this paper has compared “liǎng” in these aspects with their Thai translation and also presents some approaches on how to teach it.